Carbon microspheres prepared from the hemicelluloses-rich pre-hydrolysis liquor for contaminant removal - Wang, Yuanyuan; Cao, Xuefei; Sun, Shaoni; Zhang, Ruochen; Shi, Quentin; Zheng, Lu; Sun, Runcang (Carbohydrate polymers, 2019)
[Display omitted] •Pre-hydrolysis liquor is a promising feedstock to produce carbon microspheres (CM).•CM prepared from the PHL reduces the pollution load of the PHL significantly.•Sulfuric acid and lignin can significantly improve the formation of CM.•The functionalized CM showed good adsorption capacities for Pb(II) ion and MB. Pre-hydrolysis liquor (PHL) from the kraft-based dissolving pulp process contains large amounts of hemicelluloses, which is usually treated as an effluent and further efforts have to be involved to eliminate the pollution disposal. However, the hemicelluloses-rich PHL is a promising candidate for the production of carbon microspheres via hydrothermal carbonization. The yield of the carbon microspheres directly derived from the hydrothermal carbonization of the hemicelluloses-rich PHL (22.1%) was almost twice than that from xylose (13.1%). Furthermore, sulfuric acid and the lignin in the PHL could significantly improve the yield and change the size of the carbon microspheres obtained from the PHL. Additionally, the activated carbon microspheres functionalized with acrylic acid showed improved adsorption capacities for Pb(II) ion (273.4 mg/g) and methylene blue (701.3 mg/g). The hydrothermal carbonization of the PHL not only utilizes the hemicelluloses in the PHL, but also reduces the pollution load of the PHL significantly.